Gaya Komunikasi Ibu-Ibu di Era Digital Melalui Media Sosial Tiktok - Salma Besariani; Anisti; Tuty Mutiah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
The advancement of digital technology has significantly transformed communication patterns in society, including among housewives. TikTok has emerged as a prominent social media platform that enables this shift in communication style from conventional, domestically confined interactions to more open, interactive, and creative expressions. This study aims to analyze how mothers develop and adapt their communication styles through TikTok, using Everett M. Rogers’ Diffusion of Innovations Theory as the analytical framework. This research employs a qualitative descriptive method with in-depth interviews conducted with two active TikTok user informants. The findings reveal that both informants successfully went through the five stages of innovation diffusion: knowledge, persuasion, decision, implementation, and confirmation. Their communication styles include personal narratives, educational content, promotional messaging, and expressive visual communication. TikTok functions not only as a communication medium but also as a platform for social identity formation, digital literacy development, and economic opportunity. These results indicate that mothers are an adaptive social group capable of becoming active communicators in the digital era.